PENGARUH MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY TERHADAP HASIL BELAJAR SISWA KELAS X PADA KONSEP DINAMIKA PARTIKEL - Iwan Permana Suwarna (TARBIYA: Journal of Education in Muslim Society, 2014)
Abstract: This research aims to determine the effect of learning media based on Augmented Reality to learning outcome of students 10th grade on the concept particle dynamics. This research was done in 10th grade science class: 2 and 4 in SMA 67 Jakarta. The research was done in October-November 2013. The research method is a quasi experimental with a noneqiuvalent control group design and the sampling technique is purposive. Instruments of the research are test (multiple choices) and non test(questionnaire). Data were analyzed quantitatively using the t test, questionare analyzed qualitatively. The conclution : there is the influence of augmented reality-based instructional media on learning outcome of students grade 10th on the concept particle dynamics. Average learning outcome experiment group is higher than control group. The experimental group superior on cognitive level (C1-C4). Carrying capacity of the media Augmented Reality on the learning process had teacher done is excellent category (83.24 %). DOI: 10.15408/tjems.v1i1.1111